Evaluating Round Table and Peer Tutoring Methods on Student Motivation: A Qualitative Study in an Indonesian High School - Refiana Novita Sari; Meilia Rosani; Sri Wahyu Indrawati (PPSDP International Journal of Education, 2026)
This study aims to evaluate the effectiveness of the round table and peer tutoring learning methods in increasing the learning motivation of tenth-grade students at SMA Negeri 15 Palembang. The research is grounded in the need for innovative teaching strategies that promote active student participation and enhance conceptual understanding through group interaction and collaboration among peers. The Round Table model emphasizes cooperation and active communication in small groups, while peer tutoring involves students with greater subject mastery assisting their classmates in understanding the material. This study employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. Informants include the principal, vice principal of curriculum affairs, teachers, and tenth-grade students. The findings indicate that both methods significantly improve students’ motivation and engagement in learning. Supporting factors include teacher readiness, adequate facilities and infrastructure, and a collaborative learning environment. However, challenges such as limited implementation time and varying levels of student engagement within groups remain. Overall, the combination of the round table and peer tutoring methods has proven to be effective and serves as a viable alternative in enhancing students’ learning motivation.